(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In recent years, the number of endocrine diseases, in particular thyroid pathologies, has been increasing under the influence of environmental factors. The Aral Sea region is of particular importance as a zone of ecological crisis, where salts, chemicals and radionuclides in water and air lead to the growth of endemic goiter and oncological diseases. Thyroid cancer (TC) is one of the most common malignant tumors of the endocrine system. Its early diagnosis is of decisive importance in improving the prognosis of patients.